Variants of Novel Immunomodulatory Fc Receptor Like 5 Gene Are Associated With Multiple Sclerosis Susceptibility in the Polish Population - Chorazy, Monika; Wawrusiewicz-Kurylonek, Natalia; Adamska-Patruno, Edyta; Czarnowska, Agata; Zajkowska, Olga; Kapica-Topczewska, Katarzyna; Posmyk, Renata; Kretowski, Adam Jacek; Kochanowicz, Jan; Kułakowska, Alina (Frontiers in Neurology, 2021)
Fc receptors have been shown to play a role in several autoimmune diseases. We aimed to test, for the first time, whether some of the single nucleotide variants in the FCRL5 gene were associated with multiple sclerosis (MS) susceptibility and clinical manifestations in the Polish population. The case-control study included 94 individuals with MS and 160 healthy subjects. We genotyped two single nucleotide variants of the FCRL5 gene: rs2012199 and rs6679793. The age of onset, disease duration, and clinical condition of the MS subjects were analyzed. For statistical analysis, we used the chi-squared test confirmed with Fisher's exact test. We observed the significant differences in the distribution of investigated FCRL5 genotypes between MS subjects and healthy controls. The CC and CT genotypes, as well as the C allele of rs2012199, were significantly more common in the MS subjects, as were genotypes AA and AG, and allele A of rs6679793. We noted that decreased MS susceptibility was associated with the T allele rs2012199 (OR = 0.37, p = 0.0002) and G allele rs6679793 (OR = 0.6, p = 0.02). Our results support the role of the FCRL5 locus in MS predisposition and extend the evidence of its influence on autoimmunity.